The Multifunctional Role of Mosques in the Development of Islam: A Case Study of Al-Malik Khalid Mosque, Universiti Sains Malaysia, and Its Implications for the Nigerian Context - Auwal Salisu; Rufa'i Sulaiman Abubakar (International Journal of Religious and Interdisciplinary Studies, 2024)
This study investigates the multi-functional role of mosques in contemporary Islamic societies by examining the case of Masjid Al-Malik Khalid at Universiti Sains Malaysia. While mosques are traditionally viewed as places of worship, this study argues that they can serve as dynamic centers for Islamic development, addressing broader community needs. Through qualitative analysis of archival documents, programmatic materials, and interviews with key stakeholders, the study examines how Masjid Al-Malik Khalid goes beyond ritual practice to encompass educational initiatives, social welfare programs, financial empowerment schemes, and community outreach efforts. The findings highlight the mosque's success in fostering spiritual growth, promoting knowledge acquisition, enhancing social well-being, and empowering the Muslim community. Drawing upon the Malaysian context, the study explores the potential for replicating such multi-functional mosque models in other settings, particularly in the Nigerian context. By analyzing the challenges and opportunities of different socio-cultural contexts, this research contributes to a nuanced understanding of how mosques can serve as catalysts for holistic Islamic development in the 21st century.